An integration protocol for aligning intraoral scans to facial scans using the nasal geometry reference in a fully dentate patient. - Elbashti, Mahmoud E.; Aswehlee, Amel; Yuka Sumita; Schimmel, Martin; Abou-Ayash, Samir; Molinero-Mourelle, Pedro (Quintessence International, 2024)
Advanced digital technologies have rapidly been integrated into prosthodontics to improve the digital workflow for prosthetic rehabilitation. The integration of 3D datasets acquired from various imaging sources such as intraoral scanners and facial optical scanners allows the creation of virtual patients to perform presurgical simulation and prosthetic rehabilitation. The presented technique introduced a straightforward protocol for aligning intraoral scans (Trios 4, 3Shape) to optical face scans (Face Hunter, Zirkonzahn) using a global best-fit algorithm of 3D evaluation software (GOM Inspect). Nasal geometry data were used as the matching reference to produce virtual dental patients. This integration protocol ensured that the intraoral scanner (Trios 4, 3Shape) was used not only to scan dental arches but also used effectively to scan the nose. These scans along with professional facial scans can be successfully aligned to produce virtual dental patients. As only a single fully dentate patient case with an alignment deviation of 243.6 µm was used, further research to evaluate the accuracy of this protocol is needed.